Computational recognition and analysis of hitherto uncharacterized nucleotide cyclase-like proteins in bacteria. Issue 1 (December 2016) - Ramakrishnan, Gayatri; Jain, Abha; Chandra, Nagasuma; Srinivasan, Narayanaswamy
Abstract Evolutionary relationship between class III nucleotide cyclases and an uncharacterized set of bacterial proteins from Actinobacteria, Bacteroidetes and Proteobacteria has been recognized and analyzed. Detailed analyses of sequence and structural features resulted in the recognition of potential cyclase function conferring residues and presence of signature topological motif (βααββαβ) in the uncharacterized set of bacterial proteins. Lack of transmembrane domains and signal peptide cleavage sites is suggestive of their cytosolic subcellular localization. Furthermore, analysis on evolutionarily conserved gene clusters of the predicted nucleotide cyclase-like proteins and their evolutionary relationship with nucleotide cyclases suggest their participation in cellular signalling events. Our analyses suggest expansion of class III nucleotide cyclases. Reviewers This article was reviewed by Eugene Koonin and Michael Gromiha.